Validity of vertical jump measurement devices - Buckthorpe, M.; Morris, J.; Folland, J. P. (Journal of Sports Sciences, 2012)
Vertical jump height is thought to provide a valuable index of muscular power, which is an important factor in sports performance and for assessing the mobility and functional capacity of injured or aged individuals. The purpose of the present study was to investigate the criterion validity of four popular devices for measuring vertical jump height. A belt mat, contact mat, portable force plate, and Vertec were compared to a criterion device, a laboratory force plate. Forty participants performed three maximal countermovement jumps on each device in a counterbalanced order, using block randomization. The criterion device presented the highest mean value (50.3 cm). The portable force plate and belt mat devices recorded similar jump height values to the criterion device (within 1 cm). The contact mat and Vertec devices recorded significantly lower values than the criterion device (P < 0.001). The mean difference ± limits of agreement were: belt mat -0.1 ± 5.5 cm, contact mat -11.7 ± 6.4 cm, portable force plate -0.8 ± 3.9 cm, and Vertec -2.4 ± 6.6 cm. In conclusion, the portable force plate and belt mat devices provided valid measures of vertical jump height, whereas the Vertec and contact mat devices did not.